﻿Genetic variation and phylogenetic relationships of commercial populations of Bombus ignitus (Hymenoptera, Apidae) with wild populations in Eastern Asia - Saeed Mohamadzade Namin; Jiaxing Huang; Jiandong An; Chuleui Jung (Journal of Hymenoptera Research, 2023)
The bumblebee, Bombus ignitus (Hymenoptera, Apidae), plays a vital role in pollination in Northeast Asia, including Korea, China, Japan, and Far East Russia. Understanding the genetic makeup of the population can aid in its conservation. This study explores the DNA barcode region of cytochrome C oxidase subunit I (COI) of B. ignitus in commercial populations from Korea and Japan. The results reveal low intraspecific genetic diversity among commercially reared populations, with a maximum sequence divergence of 0.3%. Analysis of a 458-bp region of the COI gene, including 384 previously reported sequences, identified 20 haplotypes with the highest sequence divergence of 2.01% in East Asia. Commercial populations show a genetic similarity primarily with the Japanese population. Cross-mating with native populations could result in competition and genetic contamination, leading to reduced fitness and sensitivity to future environmental conditions. Morphological similarities make monitoring of such effects challenging. This study provides a basis for further research on population studies, conservation, and commercialization of local populations of B. ignitus for better pollination services while minimizing risks of reducing genetic diversity and increasing competition between native and introduced populations.